Toward Pyridine-Fused Selenium-Containing Antioxidants - Fenner, Tahli (Molecules, 2004)
Photolysis of the thiohydroximate ester derivative 21 of 2-carboethoxy-2-(2-(benzylseleno)pyridin-3-yl)tridecylcarboxylic acid (20) affords 2-dodecyl-2-carboethoxy-2,3-dihydroselenolo[2,3-b]pyridine (22) in 89% yield in a process presumably involving intramolecular homolytic substitution by a tertiary alkyl radical at selenium with loss of a benzyl radical. Work toward extending this methodology to the preparation of pyridine-fused selenium analogues of antioxidants is described.